Equilibrium, Kinetic and Thermodynamic Study on Malachite Green dye Removal from Aqueous Solution using Activated Los Pantanos De Villa Nano Carbon - Murugan, S Om; Arivoli, S (IJRDO-Journal of Applied Science, 2017)
The research of the present work was to investigate the removal of Malachite Green dyefrom aqueous solution by using Los Pantanos De Villa Nano Carbon (ALPNC). Generally, dyesare used in chemical, textile, paper, printing, leather, plastics and various food industries. Theneed for the treatment of dye contaminated waste water passed out from the industry. In thisstudy, Los Pantanos De Villa Nano Carbon was studied for its potential use as an adsorbent forremoval of Malachite Green dye. The various factors affecting adsorption, such as initial dyeconcentration, contact time, adsorbent dose, effect of temperature and pH were evaluated. Theexperimental data were fitted into the pseudo-second order kinetic model. The equilibrium ofadsorption was modeled by using the Langmuir and Freundlich isotherm models. The objectiveof the present work suggests the ALPNC may be utilized as a low cost adsorbent for MalachiteGreen dye removal from aqueous solution.